The Eliassen-Palm flux tensor - Maddison, JR; Marshall, D (2013)
The aim of this paper it to derive general coordinate-invariant forms of the Eliassen-Palm flux tensor and thereby characterize the true geometric nature of the eddy-mean-flow interaction in hydrostatic Boussinesq rotating fluids. In the quasi-geostrophic limit previous forms of the Eliassen-Palm flux tensor are shown to be related to each other via a gauge transformation; a general form is stated and its geometric properties are discussed. Similar methodology is applied to the hydrostatic Boussinesq Navier-Stokes equations to re-derive the residual-mean equations in a coordinate-invariant form. Thickness-weighted averaging in buoyancy coordinates is carefully described, via the definition of a volume-form-weighted average, constructed so as to commute with the covariant divergence of a vector. The procedures leading to the thickness-weight averaged equation are discussed, and forms of the Eliassen-Palm flux tensor which arise are identified. © 2013 Cambridge University Press.